Insects at school: teaching approaches to insects in basic education (Research, Society and Development, 2021)
The Insecta class comprises the group of organisms with the greatest diversity on Earth, they have a wide distribution and richness of species and it is possible to find them at all times of the year. Insects have become extremely important elements, as they participate in all biological processes. This work aimed to promote knowledge about insects, through the realization of didactic approaches, in order to awaken the participation and curiosity of students about insects. In this sense, the extension project "Insects at School", developed several activities such as biological models, entomological boxes, games, microscopy activities, in order to inform about the role and relationship of insects to the environment and biodiversity, beings human resources, agriculture and the economy. Activities took place weekly. Interaction with students was possible, eliminating doubts and curiosities about insects and their creation, allowing for an understanding of the main groups of insects found in their daily lives. Students were able to understand the characteristics that each group of insects has, relating them to the various aspects related to their way of life, behavior and classification, which facilitated the association between theory, arousing students' curiosity and interest in the study of insects, in addition to having shown to be important in the process of developing meaningful learning of students. With the activities developed, it was observed that the project served as a bridge between academia and the social environment, constituting a fundamental tool in the teaching of science and biology.